Normal values of radiographic measurements used for the assessment of adult hip dysplasia; analysis of 1732 healthy hips in Anatolian population - Ege, Tolga; Köse, Özkan; Demiralp, Bahtiyar; Bek, Doğan; Sanal, Tuba (Gulhane Medical School, University of Health Sciences, 2016)
Objectives: The purpose of this study is to determine the normal values of radiographic measurements used for the assessment of hip joint, particularly focusing on the hip dysplasia, on healthy young adults in Anatolian population. Materials and methods: This prospective study consisted 866 subjects ( > 18 years of age) without clinical evidence of hip disorder who underwent anterior-posterior (AP) x-ray of pelvic region for routine screening in our institution. Acetabular angle of Sharp, center edge angle, ACM angle, acetabular index, and Reimer's migration index were measured. Normative data regarding radiographic parameters were presented for both gender and body side and statistical comparison was performed between gender and body sides. Results: CE angles (M: 30.3±3.4 vs F: 28.8±2.7) and ACM (M: 41.0±1.8 vs F: 40.5±1.8) angles were higher in male subjects; AI (M: 3.5±0.6 vs F: 3.8±0.9) and Sharp angle (M: 37.9±2.5 vs F: 38.5±2.1) was higher in female subjects. Reimer's migration index was similar between genders (M: 12.6±3.5 vs F: 13.0±3.6). All measured variables were statistically different between body sides, except AI in male subjects. Conclusion: We emphasize that normal limits of acetabular angles obtained from our own population should be used as reference values in various orthopedic operations regarding acetabular region.

Çalışmanın amacı, sağlıklı Anadolu insanında kalça ekleminin, özellikle de kalça displazinin değerlendirilmesi amacı ile normal radyolojik parametrelerinin saptanmasıdır. Hastalar ve metot: Prospektif olarak yapılan çalışmamıza, klinik olarak herhangi kalça rahatsızlığı bulunmayan ve merkezimizde rutin tarama amaçlı pelvik bölgeyi içeren, ön-arka direkt grafisi çekilmiş 866 erişkin hasta ( 18 yaşından büyük) dahil edilmiştir. Asetabular Sharp açısı, CE açısı, asetabular indeks (AI), ACM açısı ve Reimer’in migrasyon indeksi standart radyografiler üzerinden ölçüldü. Her iki cinsiyet ve her iki taraf kalça için ayrı olarak normal değerler saptanıp istatistiksel karşılaştırma yapılmıştır. Sonuçlar: CE (E: 30.3±3.4 - K: 28.8±2.7) ve ACM açıları (E: 41.0±1.8 - K: 40.5±1.8) erkek hastalarda istatistiksel olarak yüksek iken; AI (E: 3.5±0.6 -K: 3.8±0.9) ve Sharp açıları (E: 37.9±2.5 -K: 38.5±2.1) bayanlarda daha fazla idi. Reimer’in migrasyon indeksi cinsiyetler arasında benzer değerlere sahipti (E: 12.6±3.5-K: 13.0±3.6). Erkek hastalardaki AI (asetabular indeks) açıları haricinde tüm parametreler her iki cinste de sağ ve sol kalça için farklı idi. Çıkarımlar: Asetabular bölgeyi içeren ortopedik cerrahi işlemlerde kendi toplumumuzdan elde edilmiş normal asetabular açı değerlerinin kullanılmasını vurgulamaktayız.
Erişkin kalça displazisinin değerlendirilmesinde normal radyolojik ölçüm değerleri; Anadolu toplumunda 1732 sağlıklı kalçanın değerlendirilmesi
Keywords: Acetebular Dysplasia; Acetebular Index; ACM Angle; Center Edge Angle; Normative Data; Reimer's Migration Index; Sharp Angle; Turkish Population; Astebular Displazi; Sharp Acısı; Aseyabular İndeks; Merkez Kenar Acısı; ACM Acısı; Reimer’in Migrasyon İndeksi; Türk Popülasyonu; Normal Data